Meaning of Work-life Balance for Workers With Disabilities - Jiwon Kim (Elsevier, 2024)
Background: This article aims to show that work-life balance (WLB) for workers with disabilities can have important meanings that can affect turnover intention and exclusion from the labor market. Methods: Using the Korean Panel Survey of Employment for the Disabled (1st-8th), panel logit models were applied to analyze the effect of WLB on the voluntary turnover intention and behavior of workers with disabilities. WLB types were categorized into four groups (Work-Life Dissatisfaction Group, Only Work Dissatisfaction Group, Only Life Dissatisfaction Group, and Work-Life Balance Group) based on the integration of job satisfaction and life satisfaction. Results: Turnover intention was significantly higher in the work-life imbalance groups (Work-Life Dissatisfaction Group, Only Work Dissatisfaction Group), which is commonly associated with job dissatisfaction. The effect of WLB on turnover intention was 1.38 times higher in Only Work Dissatisfaction Group (β: 2.25, 99% confidence interval [CI]: 1.50, 2.31), characterized by dissatisfaction solely with their job, than in Work-Life Dissatisfaction Group (β: 1.90, 99% CI: 1.97, 2.53), which was experiencing dissatisfaction with both work and life. Only Work Dissatisfaction Group resulted in actual turnover, with females (β: 0.73, 95% CI: 0.37, 1.09) more likely to exit the labor market and males (β: 0.66, 99% CI: 0.41, 0.89) showing a higher tendency to change jobs. Conclusion: WLB policy should focus on job dissatisfaction, a key predictor of turnover intention that leads to actual turnover behavior. Furthermore, women workers with disabilities are a priority policy target group to prevent exclusion from labor.